Penggunaan Media Kartu Bergambar untuk Meningkatkan Kosakata Bahasa Arab Siswa Kelas IV SDIT Al-Fadiyah Gowa - Royhan Jamil Al-Arqomi; Ambo Dalle; Ahmad Sirfi Fatoni (Jurnal Riset Rumpun Ilmu Bahasa, 2025)
This study aims to comprehensively describe the planning, implementation, and outcomes of efforts to improve students’ mastery of Arabic vocabulary through the use of picture card media in learning activities. This research employs a Classroom Action Research (CAR) design conducted in two cycles, with each cycle consisting of two meetings. The subjects of this study were 26 fourth-grade students of SDIT Al-Fadiyah Gowa. Data were collected through vocabulary mastery tests as well as teacher and student observation sheets. The planning stage was carried out collaboratively with the teacher by preparing appropriate learning instruments, while the implementation of the actions was systematically monitored using observation guidelines. The results indicate a significant improvement in students’ Arabic vocabulary mastery. In the first cycle, the average learning achievement reached 70%. After refining the instructional strategies in the second cycle, the achievement increased to 86%, showing a 16% improvement. These findings demonstrate that the use of picture card media is effective in creating more engaging, interactive, and meaningful learning experiences. Consequently, it contributes positively to enhancing the Arabic vocabulary mastery of fourth-grade students in a measurable and observable manner.